Penerapan Model Project-Based Learning Untuk Meningkatkan Hasil Belajar Materi Keragaman Budaya di Sekolah Dasar Indonesia - Fauziah, Anisa; Imaniah, Riksa Suci; Sukmanasa, Elly (Universitas Negeri Padang, 2023)
The purpose of this research is to improve learning outcomes by implementing a project-based learning model. The research subjects were off class IV with 35 students at SD Negeri Polisi 2 Bogor. The results of the research show that the success of applying the project-based learning model can improve student learning outcomes. This is evidenced by the learning outcomes of cycle I of students who were declared complete as many as 16 students and as many as 20 students who did not complete. The learning completeness of classical students reached 45.7% with an average value of 69.5. While the acquisition of learning outcomes in cycle II there were 31 students or 88.6% who achieved completeness with an average score of 80.5 and 4 students or 11.4% were declared incomplete. The completeness of students learning outcomes classically in cycle II has increased compared to cycle I only reaching 45.7% increasing to 88.6% in cycle II. Thus it can be concluded that this research has a positive and significant impact on the